2017
DOI: 10.1080/15384101.2017.1295178
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 4E-BP1 activity in the mammalian oocyte

Abstract: Fully grown mammalian oocytes utilize transcripts synthetized and stored during earlier development. RNA localization followed by a local translation is a mechanism responsible for the regulation of spatial and temporal gene expression. Here we show that the mouse oocyte contains 3 forms of cap-dependent translational repressor expressed on the mRNA level: 4E-BP1, 4E-BP2 and 4E-BP3. However, only 4E-BP1 is present as a protein in oocytes, it becomes inactivated by phosphorylation after nuclear envelope breakdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 76 publications
6
52
0
Order By: Relevance
“…In conclusion, using a chemoproteomic approach, we have discovered that CDK4 phosphorylates 4E-BP1 during the M-to-G 1 transition, thereby maintaining capdependent translation. These findings shed further light on the cell cycle-dependent phosphorylation of 4E-BP1, the regulation of which was previously reported to be mediated by CDK1 and CDK12 in mitotic cells [29,61,62], and PLK1 and CDK1 in cells undergoing meiosis [22,32,[63][64][65]. Given this newly discovered role of CDK4, it is likely that inhibition of mitotic 4E-BP1 phosphorylation is a previously unknown function of CDK4/6 inhibitors such as palbociclib, and may explain the synergy between these drugs and mTOR inhibitors [66][67][68][69][70][71][72].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In conclusion, using a chemoproteomic approach, we have discovered that CDK4 phosphorylates 4E-BP1 during the M-to-G 1 transition, thereby maintaining capdependent translation. These findings shed further light on the cell cycle-dependent phosphorylation of 4E-BP1, the regulation of which was previously reported to be mediated by CDK1 and CDK12 in mitotic cells [29,61,62], and PLK1 and CDK1 in cells undergoing meiosis [22,32,[63][64][65]. Given this newly discovered role of CDK4, it is likely that inhibition of mitotic 4E-BP1 phosphorylation is a previously unknown function of CDK4/6 inhibitors such as palbociclib, and may explain the synergy between these drugs and mTOR inhibitors [66][67][68][69][70][71][72].…”
Section: Discussionsupporting
confidence: 69%
“…CDK12, via phosphorylation of 4E-BP1 at S65 and T70, cooperates with mTORC1 to drive selective translation of proteins involved in maintenance of the mitotic genome [29]. Additionally, CDK1, the master regulator of the G 2 /M transition, can substitute for mTORC1 to phosphorylate 4E-BP1 at the putative mTORC1 sites to activate cap-dependent translation during mitosis [30,31] and meiosis [32]. A mechanistic investigation of the mitotic phosphorylation of 4E-BP1 uncovered CDK1-mediated phosphorylation of the noncanonical site S83.…”
mentioning
confidence: 99%
“…5 The current study adds new information by investigating the role of CDK1 in the phosphorylation of 4E-BP1 in mouse oocytes. 2 Using specific kinase inhibitors, they showed that CDK1 and mTOR kinases are the main positive regulators of 4E-BP1 phosphorylation following NEBD (Fig. 1).…”
mentioning
confidence: 98%
“…In this volume of the Cell Cycle the study by Jansova et al provides new insight into the role of the eukaryotic initiation factor 4E-Binding Protein 1 (4E-BP1) in meiotic spindle formation in the mouse oocyte. 2 Phosphorylation of 4E-BP1 at sites that control its binding to eIF4E, and consequently its ability to inhibit translation, has been shown to be dynamic and finely regulated in space in mitotic and meiotic spindle. 3,4 In particular, it has been proposed that the localization of 4E-BP1 isoforms that have been phosphorylated at these sites at the spindle pole or on the spindle represents a novel mechanism to localize protein synthesis from mRNAs that are localized at the spindle.…”
mentioning
confidence: 99%
See 1 more Smart Citation